1979
DOI: 10.1002/jpln.19791420318
|View full text |Cite
|
Sign up to set email alerts
|

Der Einfluß der Fauna auf die Stoffverlagerung sowie die Homogenität und die Durchlässigkeit von Böden

Abstract: Unter Beschränkung auf die wichtigsten Bodentierarten (Säuger, Ameisen, Termiten, Asseln und Regenwürmer) wird deren Einfluß auf die Stoffverlagerung, auf die Homogenität und die Durchlässigkeit von Böden an Hand neuerer und älterer Literatur dargestellt. Eine Stoffverlagerung wird von fast allen Bodentieren vorgenommen, wobei Menge, Intensität und Richtung der Verlagerung von den morphologischen Eigenschaften der betreffenden Arten bestimmt wird. Von der Fauna haben nur die Regenwürmer und ihre Verwandten ein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…This may be compared with Darwin' s [1881] estimates for an English soil of an annual rate of transport of 5 mm of earthworm casts to the soil surface during a period of 10 to 20 years following a distinct reduction in land use intensity. Graff and Makeschin [1979] [Abaturov, 1968;Voronov, 1968; quoted by Graff and Makeschin, 1979]. For a clay soil, Nemec [ 1976] reported that the apparent hydraulic conductivity continued to increase for several years following the laying of pipe drainage.…”
Section: Dynamics Of Macroporositymentioning
confidence: 99%
“…This may be compared with Darwin' s [1881] estimates for an English soil of an annual rate of transport of 5 mm of earthworm casts to the soil surface during a period of 10 to 20 years following a distinct reduction in land use intensity. Graff and Makeschin [1979] [Abaturov, 1968;Voronov, 1968; quoted by Graff and Makeschin, 1979]. For a clay soil, Nemec [ 1976] reported that the apparent hydraulic conductivity continued to increase for several years following the laying of pipe drainage.…”
Section: Dynamics Of Macroporositymentioning
confidence: 99%
“…Die Untersuchungen wurden an drei monolithischen, wägbaren Lysimetern (rund, je 1 m 2 Fläche, 3 m Höhe, Anlage 1974-1979-Moritz et al, 1991 Moritz et al, 1991und Keese et ai, 1996. Im September 1994 erfolgte die Zerlegung und Untersuchung der Monolithe im Rahmen eines interdisziplinären Projektes jeweils getrennt in Schichten sowie Rand-und Kernzone.…”
Section: Materials Und Methodenunclassified
“…Similar results are reported by other studies on mole hills. Not without reason, the mole has been called a 'zoological base pump' (Graff and Makeshin 1979 ). Pocket gopher burrowing activities have comparable effects (Mielke 1977 ;Huntly and Inouye 1988 ).…”
Section: Bioturbation (Soil Mixing Aeration Translocation Of Soil Mmentioning
confidence: 99%
“…The comparatively small amount of soil translocated by sousliks can be ascribed to their foraging behavior. Sousliks graze on the ground surface, while moles search below-ground for earthworms and other invertebrates, and thus have to move comparatively more soil (Graff and Makeshin 1979 ).…”
Section: Bioturbation (Soil Mixing Aeration Translocation Of Soil Mmentioning
confidence: 99%
See 1 more Smart Citation